Mediating role of civic talk on relationship of news consumption and sense of civic responsibility among youth - Subramaniam, Tilagavati (2020)
Sense of civic responsibility is fostered and developed through frequent involvement in sharing civic knowledge and solving social problems, individually and collectively. In other words, a citizen who has attained a sense of civic responsibility would be more responsive and supportive of developmental efforts at all levels (i.e., social and political). Hence, this sense of civic responsibility is widely recognised as an important stepping-stone towards becoming a productive citizen in the future. Past studies have shown that responsibility. This research attempts to clarify the influence of news consumption from a variety of media and civic talk on the sense of civic responsibility. Using self-three Research Universities (RUs) participated in a cross-sectional survey. Sampling method used for the population of this study was stratified systematic sampling. All variables were tested for validity and reliability in a pilot test prior to the field data collection. Descriptive analysis and the Structural Equation Modelling Partial Least Squares were employed for data analysis. The result show that news consumption had no significant positive correlation with sense of civic responsibility, but civic talk had a strongly significant and positive effect on news consumption and sense of civic responsibility. Civic talk fully mediates this relationship. The variance value explains an adequate sense of civic responsibility and civic talk in this study. The predictive power (Q²) of the hypothesised relationship was strong, as it was above the cut-off point (zero) for sense of civic responsibility and civic talk. Therefore, the current study has predictive relevance values for its endogenous constructs. From a predictive viewpoint, the model in this study could be considered beneficial for the youth to develop a better sense of civic responsibility. One significant contribution of the study findings is that it has clarified the role of civic talk in the relationship between news consumption and sense of civic responsibility. A respondent with a low level of news consumption seemed to benefit from civic talk involvement and this influenced the development of his sense of civic responsibility. This result is a pertinent input that could be used to ensure a good educational outcome for students, particularly to develop a sense of civic responsibility in them.